2020
DOI: 10.21831/pep.v24i1.32603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the implementation of Indonesia Pintar program in vocational school

Abstract: The study aims to evaluate a program of channeling educational fund, Program Indonesia Pintar (PIP), for vocational school (sekolah menengah kejuruan or SMK). This research was evaluation research using mix method approach. The evaluation model used was the CIPP model covering context, input, process, and product. Respondents in the study were 702 principals, 125 student’s parents, and 15853 students of the SMKs spreading across 29 out of 34 provinces in Indonesia. Data collection techniques used were analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This research confirmed the previous research in the Bengkayang region, which also found if the invalid data, because of the no authority of the school to manage the data, make the PIP has not targeted the right student [19]. That problem will decrease the PIP distribution effectivity, especially in the vocational school cluster, because of the student are not completed their education [20].…”
Section: Input Evaluationsupporting
confidence: 87%
“…This research confirmed the previous research in the Bengkayang region, which also found if the invalid data, because of the no authority of the school to manage the data, make the PIP has not targeted the right student [19]. That problem will decrease the PIP distribution effectivity, especially in the vocational school cluster, because of the student are not completed their education [20].…”
Section: Input Evaluationsupporting
confidence: 87%
“…Process, namely looking at the planning process in terms of easing the tasks of program implementation members and assisting in the interpretation of the results; whereas product evaluation is to identify and evaluate short and long term things to facilitate program implementation in order to facilitate good products/results and measure the importance of success in efforts to fulfill goals that have been set from the beginning (Stufflebeam, 2007). Furthermore, Hamdi et al (2020) support that with the use of CIPP, they can view in detail the program's implementation so that they may explain program activities in depth and notice the difficulties encountered that might limit the sustainability of the current program. In terms of context, it can see roughly what needs the program has.…”
Section: Cipp Evaluation Modelmentioning
confidence: 84%
“…The four components of the CIPP evaluation model are: evaluating context, evaluating input, evaluating process, and evaluating the product. The CIPP model may help get more in-depth information on data collecting, give detailed illustrations, and depict actual conditions in terms of current or finished programs (Hamdi et al (2020), As a result, the evaluator must evaluate these four characteristics while evaluating the program to determine the effectiveness of an activity up to the point of accomplishing the predetermined goals.…”
Section: Cipp Evaluation Modelmentioning
confidence: 99%
“…Dalam upaya menerapkan model penjaminan mutu pendidikan ini maka perlu adanya komitmen yang tinggi, penilaian kebutuhan, perencanaan strategik, penyusunan rencana taktis, dan penilai kemajuan. Penerapan penjaminan mutu ini sangat penting dalam penerapan manajemen pendidikan berbasis sekolah (Hamdi et al, 2020).…”
Section: Implementasi Dan Proses Penjaminan Mutu Sekolah Dasarunclassified